COMPARISON OF ORAL VERSUS INTRAVENOUS CLODRONATE IN PATIENTS WITH SKELETAL METASTASIS WITH RESPECT TO BONE MINERAL DENSITY AND PAIN SCORE - Syed, Abdus Samad; Samad, Fauzia Abdus (Pakistan Journal of Physiology, 2017)
Background: Clodronate is a bisphosphonate available both in oral as well as intravenous formulations. It is one of the effective drugs painful skeletal metastasis. The present study aimed at comparison of oral vs intravenous formulation with regard to improvement in bone mineral density and pain score among patients having skeletal metastasis. Methods: Two hundred patients having any cancer with skeletal metastasis were included in the study. They were given either oral Clodronate or intravenous Clodronate for six months and a comparison was made between them with regard to improvement in bone mineral density and pain score. Results: Out of 200 patients 135 were males and 65 females with a mean age of 54 years. Mean T score of patients on oral treatment before start of treatment was -2.42 that improved to -2.15 (p<0.005) after 6 months of therapy. Mean T-score of patients on intravenous therapy at baseline was -2.37 also improved to -2.11 (p<0.005) after 6 months of therapy. The two arms of treatment did not show statistically significant difference in pre- and post-treatment T scores. The mean pain score of the patients receiving oral Clodronate at the start of treatment was 7.33 that improved to 3.13 (p<0.005) while among patients on intravenous Clodronate it improved from 7.37 to 3.11 (p<0.005). The comparative improvement in pain scores in the two arms was not significantly different (p=0.909). Conclusion: Clodronate improves both T score on DEXA-scan and pain score among patients with skeletal metastasis irrespective of the route of administration. Pak J Physiol 2017;13(4):23–5